Duplicated Renal System with H Shaped Ureter: An Extraordinary Anomaly - Fatih Akbulut; Metin Savun; Burak Ucpinar; Murat Sahan; Burak Arslan; Faruk Ozgor; Abdulmuttalip Simsek; Ahmet Yalcın Berberoglu; Murat Baykal; Murat Binbay (Case Reports in Urology)
Duplex collecting systems are the most commonly encountered anomaly of the urinary system. Complete duplex system with an H shaped ureter is a very rare situation. There are only two reported H ureter cases in the literature. Herein, we aimed to present an H shaped ureter case, which was identified while performing ureterorenoscopy to a 48-year-old female patient due to a right distal ureteral stone.